The Effect of Transformational Leadership and Work Environment on Employee Performance: The Mediating Effect of Work Discipline - Dian Wirtadipura; Wahid Sumarjo (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Low employee performance in labor-intensive industrial sectors is often driven by weak leadership, an unconducive work environment, and poor discipline, factors that ultimately impact organizational productivity. This study examines the influence of transformational leadership and work environment on employee performance, with work discipline serving as a mediating variable, within the maintenance and workshop industry in Indonesia. Data were collected from 57 employees using quantitative research methods and analyzed using path analysis. The findings show that both the work environment and transformational leadership have a major impact on work discipline and have direct consequences on performance. Additionally, work discipline has a significant effect on performance and modulates the indirect effects of environment and leadership on performance. The proposed model explains 51.6% of the variance in employee performance and 40.1% of the variance in work discipline. These results demonstrate the vital role that supportive work environments, motivating leadership, and participatory discipline systems play in improving performance in strategically significant labor-intensive industries.